set f = proj (1,2);
for x being object st x in REAL holds
ex z being object st
( z in REAL 2 & x = (proj (1,2)) . z )
proof
set y = the Element of REAL ;
let x be object ; :: thesis: ( x in REAL implies ex z being object st
( z in REAL 2 & x = (proj (1,2)) . z ) )

assume x in REAL ; :: thesis: ex z being object st
( z in REAL 2 & x = (proj (1,2)) . z )

then reconsider x1 = x as Element of REAL ;
reconsider z = <*x1, the Element of REAL *> as Element of REAL 2 by FINSEQ_2:101;
(proj (1,2)) . z = z . 1 by PDIFF_1:def 1;
then (proj (1,2)) . z = x by FINSEQ_1:44;
hence ex z being object st
( z in REAL 2 & x = (proj (1,2)) . z ) ; :: thesis: verum
end;
hence ( dom (proj (1,2)) = REAL 2 & rng (proj (1,2)) = REAL ) by ; :: thesis: for x, y being Real holds (proj (1,2)) . <*x,y*> = x
let x, y be Real; :: thesis: (proj (1,2)) . <*x,y*> = x
reconsider x = x, y = y as Element of REAL by XREAL_0:def 1;
now :: thesis: for x, y being Element of REAL holds (proj (1,2)) . <*x,y*> = x
let x, y be Element of REAL ; :: thesis: (proj (1,2)) . <*x,y*> = x
<*x,y*> is Element of 2 -tuples_on REAL by FINSEQ_2:101;
then (proj (1,2)) . <*x,y*> = <*x,y*> . 1 by PDIFF_1:def 1;
hence (proj (1,2)) . <*x,y*> = x by FINSEQ_1:44; :: thesis: verum
end;
then (proj (1,2)) . <*x,y*> = x ;
hence (proj (1,2)) . <*x,y*> = x ; :: thesis: verum